PRESERVATION AND CONSERVATION OF B.ED COLLEGE LIBRARY PRINT MATERIALS IN EAST MIDNAPORE, WEST BENGAL - Barman, Mr. Shyamapada; Vir Singh, Dr. Dharam (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2024)
This Ph.D. thesis investigates the preservation and conservation of print materials in B.Ed college libraries in East Midnapore, West Bengal. It assesses the current state, identifies challenges, and proposes strategies.